Supporting the development and improvement of teachers’ relational competency - Anders Jönsson; Jonas Aspelin; Sofia Lindberg; Daniel Östlund (Frontiers in Education, 2024)
In this paper we present experiences and findings from a research program on how to support the development and improvement of teachers’ relational competency. Outcomes of the research program include a theoretical framework encompassing different aspects of relational competency (“communicative competency,” “differentiation competence,” and “socio-emotional competency”), and studies reporting on the use of two different methodologies (digital video simulations and virtual simulations with avatars) for assessing, as well as supporting, the development and improvements of said competency. The merits and shortcomings of these methodologies are discussed, and we propose a framework that can be used in teacher education and/or for professional development of teachers’ relational competency, based on our experiences and research findings.